The stock market of Ukraine in the context of current economic transformations (Economics and region, 2025)
The article examines current trends in the development of the Ukrainian stock market amid economic instability and institutional transformations. It emphasises that the stock market, as a key mechanism for accumulating and redistributing investment resources, plays a significant role in ensuring economic growth, stimulating investment activity and developing financial infrastructure. However, the instability of the macroeconomic environment, exacerbated by military actions and external shocks, leads to structural market distortions, weakening investment signals and imbalances between the corporate and public segments. The aim of the study is to identify current trends in the functioning of the Ukrainian stock market, determine the determinants of its transformations, and justify directions for improving the effectiveness of its development in conditions of economic turbulence. The methodological basis of the article was the use of statistical and comparative analysis tools, which made it possible to analyse market dynamics and assess key quantitative indicators of the activity of organised capital markets in 2018–2024. The results of the study show uneven dynamics in stock market trading volumes, which are sensitive to macroeconomic and political factors. The peak in activity in 2021 was driven by growing confidence in the government debt market, while the sharp decline in 2022 was caused by full-scale military aggression and a crisis of investment expectations. Despite a certain recovery in 2023–2024, the market remains structurally vulnerable, as evidenced by the dominance of the government securities segment and the limited liquidity of corporate instruments. An additional indicator of the transformation processes is the reduction in the number of professional traders from 242 to 156 participants during 2018–2024, which indicates market consolidation and the exit of less adaptive players. An analysis of the activities of organised trading platforms showed an excessive concentration of turnover on certain platforms, primarily the PFTS and the Perspektyva exchange, while a number of platforms have effectively ceased operations. The growth in the volume of exchange contracts in 2023–2024 confirms the market's potential for partial recovery, but it is mainly short-term in nature and is not accompanied by a qualitative shift in the structure of instruments. The scientific novelty of the results lies in a comprehensive assessment of the transformational changes in the Ukrainian stock market from the perspective of macroeconomic shocks, the structure of participants, and institutional mechanisms of organised trading. For the first time, the relationship between the dominance of government debt instruments, the consolidation of professional participants and the stagnation of the corporate segment in the context of a war economy has been systematised. The practical significance of the article lies in identifying priority areas for the development of the stock market: diversification of financial instruments, strengthening the corporate segment, reducing dependence on government debt securities, increasing the transparency of market operations, and developing institutional infrastructure. The implementation of the proposed approaches will contribute to the formation of a sustainable model of capital market functioning, increase its competitiveness and expand its role in ensuring national investment potential.
Keywords: stock market; capital market; portfolio investments; joint investment institutions; financial potential; financial resources